Improvement of meltdown temperature of lithium-ion battery separator using electrospun polyethersulfone membranes. (19th December 2016) - Liu, Yang; Ma, Hongyang; Hsiao, Benjamin S.; Chu, Benjamin; Tsou, Andy H.
Abstract: Polyethersulfone (PES) electrospun nanofibrous membranes have been prepared and deposited on both sides of a microporous polyethylene (PE) substrate to fabricate a nanocomposite separator, which exhibits a high meltdown temperature (MDT) to prevent the thermal runaway within the battery under the condition of overcharging or abuse. To improve adhesion to electrospun PES nanofibrous membranes, the PE substrate with low surface energy and hydrophobic nature was etched with chromic acid and characterized with atomic force microscopy (AFM) and infrared spectroscopy (FTIR) techniques as well as the water contact angle test. Compared to the original film, the modified PE substrate showed a nearly 10-times increase in adhesive strength to the electrospun PES membrane. The morphology of the electrospun PES membrane, controlled by different electrospinning flow rates, was also demonstrated to have a substantial impact on adhesion, where a 5-fold increase of the adhesive strength was observed when the flow rate increased from 20 μL/min to 60 μL/min. The composite PES/PE/PES separator, structured as a PE substrate sandwiched in 2 electrospun PES membranes, maintained the low shutdown temperature (SDT) of 131 °C but achieved a significantly higher MDT of 221 °C. Furthermore, the high porosity of the electrospun PES membrane ensured that the air permeability of the separator was not sacrificed when compared with the original PE separator. Graphical abstract: Highlights: Adhesion of PE substrate to e-spun PES increased 10-fold after chromic acid treatment. Bonding strength of PES nanofibers to PE film increased with increasing spinning rate. The MDT of PES/PE/PES membrane is much higher than that of PE or commercial separator.